Olympic and paraolympic sports: coincidences, divergences and specifities under a contemporary perspective - Marques, Renato Francisco Rodrigues; Duarte, Edison; Gutierrez, Gustavo Luis; Almeida, José Júlio Gavião de; Miranda, Tatiane Jacusiel (Brazilian journal of physical education and sport, 2009)
This text presents an analysis of the adapted sport, focusing on the Paralympics games, an event realized in association with the Olympic Games. It tries to point similarities and differences between the two events, considered as forms of expression of the contemporary sport, detaching characteristics as the organization, relationship with the market and popularization forms. The main described differences refer to the genesis of the two objects, besides the largest vocation of the Olympic sport for the market insertion. As for the similarities, it stands out the presence in both of the characteristics of the modern sport generated in the XIX century, besides the similar organizational conceptual structures. It can still be pointed some specific points of the adapted sport, as own modalities as an example of the"Goalball."